THE INFLUENCE OF LENGTH OF SOAMING POWDER FISHING TOOLS ON FRESHWATER LOBSTER CATCH RESULTS(Cherax quadricarinatus) IN TELAGO VILLAGE KERINCI LAKE - Dwi Rizki Oktaviani; Lisna Lisna; Rizky Janatul Magwa; Mairizal mairizal; Yoppie Wulanda; Muhammad Hariski (JURNAL PERIKANAN TROPIS, 2025)
Kerinci Lake is a type of tectonic lake located in the Kerinci Regency, Jambi Province. The fishing gear such as tangkul/ pesap, nets (trawls), and traps (lukah) are commonly used in Telago Village. This research aims to investigate the effect of soaking duration of trap fishing gear on the catch of freshwater lobster. This research was conducted from February 27 to March 18, 2024. An experimental fishing method was employed, comparing soaking durations of 24 hours and 12 hours. Quantitative data were analyzed using frequency of occurrence, followed by T-test analysis. The results showed that a 24-hour soaking period yielded 237 lobsters with an average weight of 34.75 grams, with the highest frequency of occurrence at 44% and the lowest at 24%, averaging 33.20%. In contrast, a 12-hour soaking period resulted in 119 lobsters with an average weight of 33.88 grams, with the highest frequency of occurrence at 32% and the lowest at 8%, averaging 17.60%. T-test analysis indicated no significant effect of soaking duration on the number of lobsters caught, average weight, or depth-related environmental parameters. However, significant effects were observed for environmental parameters such as temperature and pH. In conclusion, while soaking duration does not significantly affect the catch of freshwater lobster (Cherax quadricarinatus), the 24-hour soaking period resulted in a higher yield.